Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given $(1+x^2)y''+2xy'-2y = 0$

The above equations obviously has analytic points everywhere except for $x=1$ and $-1$.

Find two linearly independent solutions $y_1$ and $y_2$ to the differential equation valid near $x_0=0$. To make life a little easier, choose the linearly independent equations:

$y_1$ $:$ $a_0$ = $y(x_0)$ = 1 and $a_1$ = $y'(x_0)$ = 0

$y_2$ $:$ $a_0$ = $y(x_0)$ = 0 and $a_1$ = $y'(x_0)$ = 1

After a mess of writing, I came up with the following:

$a_{n+2}$ = $[{-(n-1)(n)a_n - 2a_n(n-1)}]/[{(n+1)(n+2)}]$

I don't know if that monster is right, but that's where I need you help. Can somebody give this a sanity check, and then solve the rest?

share|cite|improve this question
Some more detail would be nice. What did you get after substituting your power series ansatz into your differential equation? – J. M. May 7 '12 at 1:43
I checked the series solution myself, your expression of $a_{n+2}$ looks correct to me. – Shuhao Cao May 7 '12 at 2:14
up vote 2 down vote accepted

If we set up $y = \displaystyle \sum^{\infty}_{n=1} a_n x^n$ like you did, plugging back to the original equation: $$ (-2a_0+2a_2) + 6a_3 x +\sum^{\infty}_{n=2}\Big((n+2)(n+1)a_{n+2} - (n-1)(n+2)a_n\Big)x^n = 0 $$ simplify the expression for $a_{n+2}$ when $n\geq 2$: $$ a_{n+2} = -\frac{n-1}{n+1} a_n \qquad (*) $$ for the constant and $x$-term we have: $$ a_0 = a_2, \text{ and } a_3 = 0 $$

  • Now if the initial condition is $a_0 = 1, a_1 = 0$, then we have: $$ a_2 = 1, \text{ and } a_{n+2} = (-1)^{n/2}\frac{n-1}{n+1}\cdot \frac{n-3}{n-1}\cdots\frac{1}{3} = \frac{(-1)^{n/2}}{n+1} $$ and $n$ can be even numbers, let $n = 2k$ we have the solution is: $$ y = 1+x^2 + \sum^{\infty}_{k=1}\frac{(-1)^k x^{2k+2}}{2k+1} = 1 + x\cdot \sum^{\infty}_{k=0}\frac{(-1)^k x^{2k+1}}{2k+1} = 1+ x\arctan x $$

  • Now if the initial condition is $a_0 = 0, a_1 = 1$, $a_2 = a_0 = 0$ implies all even powered $x$ coefficients are zero after $n=2$ because of the relation $(*)$, also by $(*)$ and $a_3 = 0$ we know that all odd powered $x$ coefficients are zero too after $n=3$, therefore the solution is just: $$ y = x $$

To sum up, the two linearly independent solutions are: $$y = x \;\text{ or }\; 1+ x\arctan(x)$$

share|cite|improve this answer
Thanks Jon. The only reason why I got stuck was because the simplification threw me off. It was late and I didn't even think to simplify (in fact I thought it was already simplified). Anyway, thanks again. – Nico Bellic May 7 '12 at 14:16
@NicoBellic Haha, no problem, btw I love GTA4 too! – Shuhao Cao May 7 '12 at 17:01
Haha, nice few people recognize the reference. – Nico Bellic May 7 '12 at 18:16
The power series method works well provided I can solve the recursion relation. All the textbook examples usualy lead to a recursion that involves two coefficients only ( in this case $a_{n+2}$ and $a_n$). However, in most real world examples this is not the case, ie $a_{n+2}$ is usualy a function of $a_n$ and som other values of $a$ with lower indices. How do I solve the recursion relation then? Or in other words how would I go about solving an equation $(1 + x^2)y^{''} + 2 x y^{'} -2 x y =0$ using the power expansion method? – Przemo Feb 12 '14 at 16:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.